Evaluating Intersection Performance in Response to Garuda Bridge Construction: A Case Study at Khatulistiwa -Gusti Situt Mahmud - Terminal Siantan , Pontianak - Jesnita, Jesnita; Mayuni, Siti; Said, Said (Jurnal Teknik Sipil, 2025)
The replacement of outdated transportation infrastructure can significantly influence urban traffic systems, particularly in relation to trip generation and intersection performance. In Pontianak, the Bardan ferry crossing is planned to be replaced by the Garuda Bridge, which is expected to increase traffic volumes. This study analyzes the impact of the bridge on the performance of the intersection at Jalan Khatulistiwa – Jalan Gusti Situt Mahmud – Jalan Terminal Siantan through traffic surveys and PTV Vissim simulations with projected growth rates of 6%, 9%, and 12%. The existing condition shows poor performance at Level of Service (LOS) F, with an average delay of 53.56 seconds and a queue length of 101.83 meters. Among four alternatives tested, Alternative 4—widening the main roads to 14 meters and adding continuous through lanes (LrsJT) and direct left-turn lanes (BkiJT)—proved most effective. This design improved LOS to D, reducing delays by 30.67% at 6% growth, and about 28% at 9% and 12%. While LOS B was not achieved, the Garuda Bridge significantly enhances efficiency and reduces traffic delays, highlighting its role in improving regional mobility.